PUSARAN EKONOMI DI BALIK BISNIS PROSTITUSI DI LOKALISASI DOLLY-JARAK SURABAYAMutimmatul Faidah Fakultas Teknik Universitas Negeri Surabaya genfida@yahoo.com (Lentera, Jurnal Studi Perempuan, 2014)
Abstract: The closing of Dolly and Jarak localization evoke variaty of rejection and resistance. It occurs because the localization bring a huge economical impact. There are  a  lot  of  works  and  business   that  depend  on  the  sex  trade.  This  research  is qualitative research using phenomonology approach. The object of the research is Sex Commercial Worker (PSK), pimp, and the resident around the localization. The collection  of  the  data  are  interview,  observation,  and  documentation.  The  results shows that there is a huge dependency of several businesses on the sex trade, which make localization become a central place of money circulation. As a center of the main economic business, prostitution is hardly broken off. Therefore,  the closure of the